PEMIKIRAN HUKUM TATA NEGARA FAZLUR RAHMAN - Ma'mun Mu'min (Program Studi Hukum Keluarga Islam, 2014)
Fazlur Rahman’s thought of constitutional law emphasises on certain issues: First, Islamic countries should form a democratic Islamic state. Head of State is directly elected by the people. Head of State is responsible to the people through parliament whose members are also elected by people directly. Second, relationship between Islam and the state is very close, because the foundation of the state and the system of law should come from the sources of Islam, namely the Qur’an and the Hadith. If government is violating Islamic value it is no longer credible and should be dismissed. Third, the concept of the Islamic state is debatable therefore Fazlur Rahman choses the concept of an Islamic democratic state. The head of state is elected directly by the people and the president as head of state responsible to the people through parliament. Fourth, there are many problems in the establishment of an Islamic state. According to Rahman, the establishment of an Islamic state is accomplished through a long struggle, such as the establishment of the Islamic state of Pakistan. It is started with the commitment of Muslims to carry out God’s command. The establishment of an Islamic state aims for safety and sovereignty of the country. Fifth, concerning the issue of the duty and authority of the head of state, according to Fazlur Rahman the head of state in charge of leading the government, in carrying out its duties and powers shall be in accordance with the interests of all the people.Key words: Thought, Law and State.